Influence of Age and Sex on the Pharmacokinetics of Midazolam and the Depth of Sedation in Pediatric Patients Undergoing Minor Surgeries - Carmen Flores-Pérez; Janett Flores-Pérez; Luis Alfonso Moreno-Rocha; Juan Luis Chávez-Pacheco; Norma Angélica Noguez-Méndez; Blanca Ramírez-Mendiola; Yolopsi Sánchez-Maza; Lina Sarmiento-Argüello (MDPI AG, 2023)
Whether age and sex influence the depth of sedation and the pharmacokinetics of midazolam is currently unknown. The influence of age and sex was investigated in 117 children (2 to 17 years) who required intravenous sedation for minor surgery (0.05 mg/kg). Plasma concentrations and sedation effects were simultaneously measured. The measured concentrations were analyzed using a two-compartment model with first-order elimination. Among the age ranges, significant differences were found (p < 0.05) between the volume of distribution (Vd) of the first compartment (V1) and that of the second (V2). With respect to sex, differences in V2 were found between age groups. At the administered dose, in patients younger than 6 years, a profound sedative effect (40-60 BIS) was observed for up to 120 min, while in older children, the effect lasted only half as long. The differences found in the Vd and bispectral index (BIS) in patients younger than 6 years compared to older patients may be due to immature CYP3A activity and body fat content; furthermore, the Vd varies with age due to changes in body composition and protein binding. Patients younger than 6 years require intravenous (IV) doses <0.05 mg/kg of midazolam for deep sedation. Dosage adjustments according to age group are suggested.